A review on mechanism of flood disaster management in Asia - Islam, Rabiul; Kamarudin, Roslina; Ahmad, Siti Aznor; Soon, Jan Jan; Anuar, Abdul Rahim (2016)
This paper attempts to analyze the review on mechanism of flood disaster management in Asia. Flood is among st the most common of natural disasters and its impact is one of the most significant disasters in the world. In this paper, we have discussed the flood disaster management some selected countries in Asia such as Malaysia, Indonesia, Thailand, Bangladesh, India, Pakistan, Japan and China.For these countries, we tried to explore the flood disaster risk, pre- and post-disaster program and participants, emergency response and recovery, flood mitigation and management, relief and preparedness machinery, flood forecasting and warning system, policy, planning as well as strategic etc.This paper can make for the above countries disaster management system better respond and handle to disasters risk, and reduce the social and economic losses of disasters caused.It also required to improve data availability and evaluation, and possibly to combine with other types of information in view of increasing usefulness for policy making.